Effects of seed priming treatments on the germination and development of two rapeseed (Brassica napus L.) varieties under the co-influence of low temperature and drought. - Zong He Zhu (Public Library of Science (PLoS), 2021)
The present study was performed to evaluate the effects of seed priming. This was done by soaking the seeds of two rapeseed cultivars, namely, ZY15 (tolerant to low temperature and drought) and HY49 (sensitive to low temperature and drought), for 12 h in varying solutions: distilled water, 138 mg/L salicylic acid (SA), 300 mg/L gibberellic acid (GA), 89.4 mg/L sodium nitroprusside (SNP), 3000 mg/L calcium chloride (CaCl2), and 30 mg/L abscisic acid (ABA). Primed and non-primed seeds were left to germinate at 15°C and -0.15 MPa (T15W15) and at 25°C and 0 MPa (T25W0), respectively. The results showed that SA, GA, SNP, CaCl2, and ABA significantly improved the germination potential (GP), germination rate (GR), germination index (GI), stem fresh weight (SFW), stem dry weight (SDW), root length (RL), stem length (SL), and seed vigor index (SVI) under T15W15. For ZY15 seeds under T25W0, GA, SNP, CaCl2, and ABA priming reduced the average germination time (96% after 5 days) compared to that of the control (88% after 5 days). For ZY15 seeds under T15W15, SA, SNP, CaCl2, and ABA priming, with respect to the control and water-treated groups, shortened the average germination time (92% after 5 days) compared to that of the control (80% after 5 days). For HY49 seeds under T25W0, GA, SNP, CaCl2, and ABA priming reduced the average germination time (92% after 5 days) compared to that of the control (85% after 5 days). Similarly, for HY49 seeds under T15W15, GA priming shortened the average germination time (89% after 5 days) compared to that of the control (83% after 5 days). These priming agents increased the net photosynthesis, stomatal conductivity, and transpiration rate of rape seedlings under conditions of low temperature and drought stress, while also decreasing intercellular carbon dioxide (CO2) concentrations. Additionally, SA, GA, SNP, CaCl2, and ABA increased superoxide dismutase concentrations (SOD) and ascorbic peroxidase (APX) activities of rape seedlings under stress conditions, while decreasing catalase (CAT) and peroxidase (POD) activities in ZY15 seedlings. In HY49, which is sensitive to low temperature and drought, all priming solutions, except for SNP, led to an increase in SOD activity levels and a decrease in CAT activity levels. Overall, SA, GA, SNP, and CaCl2 increased the concentrations of indoleacetic acid (IAA), GA, ABA, and cytokinin (CTK) in seedlings under stress conditions. Moreover, compared to SA, CaCl2, and ABA, GA (300 mg/L) and SNP (300 mol/L) showed improved priming effects for ZY15 and HY49 under stress conditions.